Human obesity and endothelium-dependent responsiveness - Campia, Umberto (Blackwell Publishing Ltd, 2012)
Obesity is an ongoing worldwide epidemic. Besides being a medical condition in itself, obesity dramatically increases the risk of development of metabolic and cardiovascular disease. This risk appears to stem from multiple abnormalities in adipose tissue function leading to a chronic inflammatory state and to dysregulation of the endocrine and paracrine actions of adipocyte-derived factors. These, in turn, disrupt vascular homeostasis by causing an imbalance between the NO pathway and the endothelin 1 system, with impaired insulin-stimulated endothelium-dependent vasodilation. Importantly, emerging evidence suggests that the vascular dysfunction of obesity is not just limited to the endothelium, but also involves the other layers of the vessel wall. In particular, obesity-related changes in medial smooth muscle cells seem to disrupt the physiological facilitatory action of insulin on the responsiveness to vasodilator stimuli, whereas the adventitia and perivascular fat appear to be a source of pro-inflammatory and vasoactive factors that may contribute to endothelial and smooth muscle cell dysfunction, and to the pathogenesis of vascular disease. While obesity-induced vascular dysfunction appears to be reversible, at least in part, with weight control strategies, these have not proved sufficient to prevent the metabolic and cardiovascular complication of obesity on a large scale. While a number of currently available drugs have shown potentially beneficial vascular effects in patients with obesity and the metabolic syndrome, elucidation of the pathophysiological mechanisms underlying vascular damage in obese patients is necessary to identify additional pharmacologic targets to prevent the cardiovascular complications of obesity, and their human and economic costs. LINKED ARTICLES: This article is part of a themed section on Fat and Vascular Responsiveness. To view the other articles in this section visit http://dx.doi.org/10.1111/bph.2012.165.issue-3